RAZUM U SENCI AFEKTA ILI NOVO LICE NOVIH MEDIJA: Zizi Papacharissi, Affective Publics: Sentiment, Technology, and Politics. New York, NY: Oxford University Press, 2015. - Loš, Tatjana (POLITEIA, 2021)
Prikaz knjige:Zizi Papacharissi, Affective Publics: Sentiment, Technology, and Politics. New York,  NY: Oxford University Press, 2015.
Keywords: prikaz knjige; afekt; mediji; twitter